Volatility and the cross-section of returns on FX options - Fullwood, Jonathan; James, Jessica; Marsh, Ian W. (Journal of Financial Economics, 2021)
We study the cross-section of returns on FX options sorting currencies based on implied volatilities (IVs). Long straddle positions in currencies with low (high) IVs perform well (poorly). A long low IV-short high IV strategy produces large average returns after transaction costs. Total volatility matters rather than any component or transformation of volatility. The returns are distinct from those in the literature on foreign exchange returns or equity option returns and cannot be explained convincingly by standard risk factors. We argue cross-sectional differences in hedging demand combined with limits to arbitrage contribute to mispricing in FX options.